sdrH enhances Staphylococcus aureus infection in diabetic wounds - Nie, Kaiyu; Wang, Kaiyu; Wen, Yin; Peng, Jinmei; Tang, Shijie (Frontiers in Microbiology, 2025)
IntroductionDiabetes mellitus is a widespread chronic condition that can lead to a variety of complications. Among the numerous complications associated with diabetes, diabetic foot ulcers are particularly notable due to their high prevalence and potential severity. These ulcers are characterized by a substantial incidence rate, a considerable risk of infection, and a high probability of necessitating amputation. Staphylococcus aureus, a notorious pathogen within this context, exacerbates wound pathogenesis and can facilitate ulcer extension and, in severe instances, gangrene through the secretion of numerous virulence factors.MethodsRT–qPCR was used to analyze the expression of Staphylococcus aureus adhesin virulence factors. Utilizing gene knockout techniques to deleted the sdrH and icaA-C genes. Biofilm formation of S. aureus was observed by scanning electron microscope. The effect of sdrH and icaA-C genes on S. aureus infected wound healing was also evaluated using a diabetic mice skin wound infection model.ResultsThe sdrH gene and the icaA-C gene cluster are critical contributors to Staphylococcus aureus infection in diabetic wounds. Post-infection with the sdrH single-gene knockout strain, a significant enhancement in wound healing rates was observed, accompanied by a marked reduction in bacterial colonization per unit area. Conversely, no significant differences were detected between the icaA-C gene cluster knockout strain and the wild-type strain. Compared to infections caused by either the wild-type strain or the sdrH single-knockout strain, infection with the icaA-C/sdrH double-knockout strain led to a marked increase in the wound healing rate and a significant reduction in bacterial load.DiscussionThis study presented that the sdrH gene enhances the virulence of Staphylococcus aureus in diabetic wounds by attenuating the host immune response, reducing the infiltration of inflammatory cells, and impairing the immune system’s capacity to clear bacteria, thereby impeding the wound healing process. Although icaA-C is not a pivotal player, it seems to enhance the virulence capabilities of sdrH.